Distribution of potato (Solanum tuberosum) viruses in Kazakhstan (International Journal of Biology and Chemistry, 2018)
Potato is one of the most popular crops, cultivated around the world. The decrease in potato yield is caused by the degeneration of the seed material associated with the defeat of various diseases. Viruses pose a great threat to potato farming all over the world. Viral infections are dangerous not only by a significant decrease in the potato yield, but also by the absence of a phenotypic manifestation of diseases. The use of modern mpRT-PCR and ELISA methods for the diagnostics allows detecting viral infection quickly and reliably. The purpose of our research was to compare the efficiency of the molecular diagnostic methods of ELISA and mpRT-PCR and on their basis to study the degree of potato damage by the PLRV, PVM, PVS, PVX and PVY viruses in the southeast and north of Kazakhstan. There were analyzed 119 samples from Almaty and 138 samples from Kostanay regions. Most of tested potato samples were infected by PVM and PVS. PLRV was absent in the southeast and north of Kazakhstan. Complex viral infections were dominance over the monoviral infection. The reliability of ELISA and mpRT-PCR methods for the diagnostics of PVX, PVY, PVM, PVS and PLRV was assessed. Viruses PVS, PVX and PVY were more effectively detected by the mpRT-PCR than ELISA. ELISA was more effective for PVM. The reliability and efficiency of analytical methods highly depended on the variability of the nucleotide and amino acid sequences of virus isolates. We found two isolates of the PVS and three PVM isolates in the course of optimization of the mpRT-PCR method.